Analysis of Success and Barriers to Implementing Health Service Management Information Systems in Indonesia: Case Studies and Recent Literature Review - Samura, Jul Asdar Putra (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Digital transformation in healthcare services in Indonesia has encouraged the use of Hospital Management Information Systems (SIMRS) as a crucial instrument for improving service quality, efficiency, and accountability. However, its implementation still faces various technical and non-technical obstacles. This study employed a systematic literature review approach by analyzing ten Google Scholar-indexed articles published between 2022 and 2025. Articles were selected using the keywords